Performance of Pediatric Index of Mortality-2 in a Pediatric Intensive Care Unit of a Tertiary Care Hospital of Nepal - Dhungana, Sangita Puree; Panta, P.P.; Shrestha, S.K.; Shrestha, S. (Nepal Medical College Journal, 2019)
Various scoring system have been developed and are becoming essential part of Pediatric and other critical care units. The Pediatric department wants to introduce Pediatric Index of Mortality-2 (PIM 2) as a predictive scoring system in Pediatric critical care unit of Nepal Medical College Teaching Hospital (NMCTH). This was a prospective cohort study done in Pediatric Intensive Care Unit (PICU) of NMCTH. Study was done from August 2017 to December 2018. All cases admitted in ICU were taken consecutively from term newborn to 14 yrs of age. PIM 2 scoring system was done in all patients. PIM 2 performed well in terms of discrimination with area under curve for PIM 2 scor e was 0.809 with 95% Confidence Interval of 0.0709 to 0.910 and Standard Error of 0.051. Good calibration was observed across deciles of risk as measured by Hosmer-Lemeshow goodness of fit test with P value of 0.163, chi-square value of 11.752 (8). Mortality observed in our PICU was 28.4% with standardized mortality ratio of 1. PIM 2 scoring system performed well in our PICU.